Exploring the Benefits of Annular Rectangular Rib for Enhancing Thermal Efficiency of Nonpremixed Micro-Combustor. (13th February 2020) - Wang, Hongcai; Fang, Hongru; Lou, Bingqian; Abubakar, Shitu; Li, Yuqiang; Meng, Lei
Abstract : Micro-combustor can provide the required thermal energy of micro-thermal photovoltaic (MTPV) systems. The performance of MTPV is greatly affected by the effectiveness of a micro-combustor. In this study, a numerical simulation was conducted to explore the benefits of annular rectangular rib for enhancing the thermal performance of a nonpremixed micro-combustor. Based on the investigations under various rib heights, rib positions, and inlet mass flow rates, it is found that the addition of annular rectangular ribs in the micro-combustor creates a turbulent zone in the combustion chamber, thereby enhancing the heat transfer efficiency between the inner wall of the combustion chamber and the burned gas. The micro-combustor with annular rectangular rib shows a higher and more uniform wall temperature. When the H2 mass flow is 7.438 × 10 −8  kg/s and the air mass flow is 2.576 × 10 −6  kg/s, the optimum dimensionless rib position is at l  = 6/9 and r  = 0.4. At this condition, the micro-combustor has the most effective and uniform heat transfer performance and shows significant decreases in entropy generation and exergy destruction. However, the optimum l and r significantly depend on the inlet mass flow of H2 /air mixture.